PENINGKATAN PERILAKU RESPEK MELALUI OUTDOOR EDUCATION - Budiman, Ali (STKIP Pasundan, 2019)
This article aims to examine the effect of outdoor education activities on student respect behavior. The research method used in this study was an experimental method using the Pretest-Posttest Two Experimental Group Design. This research was conducted in Padalarang State High School 2, West Bandung Regency with a total sample of 40 students, consisting of 15 women and 25 men who were selected using simple random sampling technique. The results showed that there was a significant increase in students' respect for behavior through outdoor education activities. This research is expected to be a solution for educators to overcome the problems of moral degradation that occur among the younger generation.